Interplanetary magnetic field control of the ionospheric field‐aligned current and convection distributions. Issue 4 (16th April 2014) - Juusola, L.; E. Milan, S.; Lester, M.; Grocott, A.; M. Imber, S.
<x xml:space="preserve">Abstract</x> Patterns of the high‐latitude ionospheric convection and field‐aligned current (FAC) are a manifestation of the solar wind‐magnetosphere‐ionosphere coupling. By observing them we can acquire information on magnetopause reconnection, a process through which solar wind energy enters the magnetosphere. We use over 10 years of magnetic field and convection data from the CHAMP satellite and Super Dual Auroral Radar Network radars, respectively, to display combined distributions of the FACs and convection for different interplanetary magnetic field (IMF) orientations and amplitudes. During southward IMF, convection follows the established two‐cell pattern with associated Region 1 and Region 2 FACs, indicating subsolar reconnection. During northward IMF, superposed on a weak two‐cell pattern there is a reversed two‐cell pattern with associated Region 0 and Region 1 FACs on the dayside, indicating lobe reconnection. For dominant IMF Bx, the sign of Bz determines whether lobe or subsolar reconnection signatures will be observed, but Bx will weaken the signatures compared to pure northward or southward IMF. When the IMF rotates from northward to duskward or dawnward, the distinct reversed and forward two‐cell patterns start to merge into a distorted two‐cell pattern. This is in agreement with the IMF By displacing the reconnection location from the open lobe field lines to closed dawn or dusk field lines, even though IMF Bz>0. As the IMF continues to rotate southward, the distorted pattern transforms smoothly to that of the symmetric two‐cell pattern. While the IMF direction determines the configuration of the FACs and convection, the IMF amplitude affects their intensity.